2011
DOI: 10.1007/s00784-011-0636-6
|View full text |Cite
|
Sign up to set email alerts
|

Possible hazardous effects of hydrofluoric acid and recommendations for treatment approach: a review

Abstract: Hydrofluoric acid (HF) is commonly used for conditioning the glass ceramics either prior to cementation or for intraoral repair in prosthetic and restorative dentistry. The present study offers a review of chemical properties of HF used, highlight the possible hazardous effects of this agent, and to recommend the treatment approach for potential risks. Available published information documented in PubMed, Medline, and Picarta literature databases was reviewed. Additional information was derived from scientific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
151
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(156 citation statements)
references
References 78 publications
(124 reference statements)
1
151
0
4
Order By: Relevance
“…Hydrofluoric acid is the inorganic acid hydrogen fluoride. Industrially, hydrofluoric acid is used to etch silica-based materials, clean metal surfaces before electroplating, and etch silicon wafers in electronic semiconductor materials [47][48][49][50] . Concentrations of 4%-10% hydrofluoric acid are typically used in the dental clinic and dental laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrofluoric acid is the inorganic acid hydrogen fluoride. Industrially, hydrofluoric acid is used to etch silica-based materials, clean metal surfaces before electroplating, and etch silicon wafers in electronic semiconductor materials [47][48][49][50] . Concentrations of 4%-10% hydrofluoric acid are typically used in the dental clinic and dental laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that different treatments, such as phosphoric acid, aluminum oxide or without etching presented lower bond strength in relation to surface HF acid etching 2,11,13 . However, previous studies have shown that HF acid may promoted severe problems for dental personnel and patients because this solution is extremely toxic, reactive and corrosive 10,15 , and the severity depends on the acid concentration, exposure time and penetration into the exposed Figure 1. Frequency distributions (%) of the adhesive remnant index (ARI) scores for all groups.…”
Section: Discussionmentioning
confidence: 99%
“…HF acid is an efficient surface modification agent that is capable of dissolving the glassy ceramic matrix, increased the roughness 6 , contact surface and wettability 7,8 , promoting higher bond between bonding materials and ceramics [9][10][11] . The application of hydrofluoric acid followed by a silane solution have been used prior to bonding glass ceramic to increase the bond strength and durability between brackets and ceramic surface 3,12,13 or luting glass ceramic restorations 12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 2.5% calcium gluconate gel is often used to treat burn lesions induced by acid [6,7]. After first aid by washing and application of gel, 5% of calcium gluconate injections may be required for lesions especially of deep burns with a large surface area [5]. Severe systemic toxicity may occur following HF burns.…”
Section: Discussionmentioning
confidence: 99%